English Deutsch Français Italiano Español Português 繁體中文 Bahasa Indonesia Tiếng Việt ภาษาไทย
All categories

Can anyone answer this and PLEASE tell me how they got their answer.

Which of the following expressions represents the product of 3 less that twice x and 2 more than the quantity of 3 times x?

A. -6x squared + 25x +6
B. 6x squared + 5x + 6
C. 6x squared + 5x + 6
D. 6x squared - 5x - 6
E. 6x squared - 13x - 6

2007-11-11 17:48:03 · 6 answers · asked by Anonymous in Science & Mathematics Mathematics

6 answers

3 less than twice x = (2x-3)
2 more than 3 times x = (3x+2)

to multiply (2x-3) (3x+2), use FOIL = first, outer, inner, last
first = 2x*3x = 6x squared (also written as 6x^2)
outer = 2x * 2 = 4x
inner = -3 * 3x = -9x
last = -3 * 2 = -6

all of that together, 6x^2 + 4x - 9x - 6 =
D) 6x^2 -5x - 6

2007-11-11 17:56:07 · answer #1 · answered by lkj 1 · 0 0

The expression "3 less than twice x" can be written mathematically as (2x-3).
The expression "2 more than three times x" can be written as (3x+2).

So the product of the above two can be written as:
(2x-3)(3x+2)
Which can be simplified by multiplying the content of each bracket.
= 2x * 3x + 2 * 2x - 3 * 3x - 3 * 2
= 6x squared + 4x - 9x - 6
= 6x squared - 5x - 6

Which is the answer no. D


:)

2007-11-12 02:02:52 · answer #2 · answered by koolfuzz 1 · 0 0

You find a product by multiplication.

"3 less than twice x" = 2x - 3
"2 more than the quantity of 3 times x" = 3x + 2

Multiply the two using FOIL (First, Inside, Outside, Last):

(2x-3)*(3x+2) = (2x*3x) + (2x*2) +(-3*3x)+(-3*2)
= 6x^2 + 4x + -9x + -6
= 6x^2 -5x - 6

2007-11-12 02:01:37 · answer #3 · answered by Anonymous · 0 0

Let's break this down.
"3 less than twice x"
= 3 less than 2x
= 2x - 3

"2 more than the quantity of 3 times x"
= 2 more than 3x
= 3x + 2

"Product of 3 less than twice x and 2 more than the quantity of 3 times x"
= (2x - 3)(3x + 2)
= 6x^2 +4x - 9x - 6
= 6x^2 - 5x - 6

D. will be your answer

2007-11-12 01:55:45 · answer #4 · answered by Anonymous · 1 0

Take it step by step and convert words into an equation.

(2x - 3)(3x + 2) = 6x² + 4x - 9x - 6 = 6x² - 5x - 6

The answer is D.

2007-11-12 01:54:13 · answer #5 · answered by Northstar 7 · 2 0

use FOIL (first inside outside last)
(2x-3)(3x+2) = (2x)(3x) + 2(2x) - 3(3x) - (3)(2)
= 6x^2 + 4x - 9x - 6
= 6x^2 - 5x - 6

(D)

2007-11-12 01:57:43 · answer #6 · answered by selket 3 · 0 0

fedest.com, questions and answers